Complex Analysis - Gherardelli, F.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
A. Andreotti: Nine lectures on complex analysis.- J.J. Kohn: Propagations of singularities for the Cauchy-Riemann equations.- Yum-Tong Siu: The mixed case of the direct image theorem and its applications.
A. Andreotti: Nine lectures on complex analysis -- J.J. Kohn: Propagations of singularities for the Cauchy-Riemann equations -- Yum-Tong Siu: The mixed case of the direct image theorem and its applications.
Keywords: Mathematics; Functions of complex variables; Differential equations, partial; Mathematics; Functions of a Complex Variable; Several Complex Variables and Analytic Spaces